2022
DOI: 10.3389/fvets.2021.778556
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Gut Microbiome and Resistomes of Wild and Zoo-Captive Macaques

Abstract: Rhesus macaques (Macaca mulatta) are the most widely distributed species of Old World monkey and are frequently used as animal models to study human health and disease. Their gastrointestinal microbial community likely plays a major role in their physiology, ecology and evolution. Herein, we compared the fecal microbiome and antibiotic resistance genes in 15 free-ranging and 81 zoo-captive rhesus macaques sampled from two zoos in China, using both 16S amplicon sequencing and whole genome shotgun DNA sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 55 publications
0
2
0
1
Order By: Relevance
“…For example, a previous study on wild and captive sika deer (Cervus nippon) has proved that captivity could also affect the diversity of the gut microbiota [24]. In studies of nonhuman primates (NHPs), captivity altered the original structure of the gut microbiome shaped by natural dietary sources [9,[25][26][27] and increased the abundance and diversity of antibiotic genes [28]. Previous studies on humans and animals have suggested that many gastrointestinal (GI) diseases and metabolic diseases are strongly connected with gut microbiome disruption [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a previous study on wild and captive sika deer (Cervus nippon) has proved that captivity could also affect the diversity of the gut microbiota [24]. In studies of nonhuman primates (NHPs), captivity altered the original structure of the gut microbiome shaped by natural dietary sources [9,[25][26][27] and increased the abundance and diversity of antibiotic genes [28]. Previous studies on humans and animals have suggested that many gastrointestinal (GI) diseases and metabolic diseases are strongly connected with gut microbiome disruption [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic activities produce rapid changes in the habitat available to wildlife intensifying the interaction between wild animals, humans and domestic animals, increasing the risk of pathogen transmission (Kruse et al, 2004). The increased interaction between wild animals and the human microbiome and exposure to antibiotics has been shown to decrease bacterial diversity in the wild host, at the same time as increasing the chance for the development of pathogenic strains and increasing the prevalence of antimicrobial resistance genes (ARGs) (Fernandes et al, 2022;Jia et al, 2022). Therefore, it is important to know the genomic diversity of potential pathogens in wild animals that can be transmitted to humans and investigate their virulence and ARGs.…”
Section: Introductionmentioning
confidence: 99%
“…aumentado de disbiose(Amato et al, 2016b). Há relato de que a microbiota intestinal de Macaca mulatta em cativeiro possui maior diversidade e abundância de genes de resistência a antibióticos(Jia et al, 2022). Esta classe de genes também verificada na microbiota de Macaca fascicularis reflete variações na dieta(Yan et al, 2022).Em bugios-pretos (A. pigra), já foi verificado que ocorre uma variação na microbiota intestinal de indivíduos oriundos de diferentes habitats no México (fragmento de floresta tropical, floresta semidecídua, floresta tropical contínua e cativeiro)(Amato et al, 2013).…”
unclassified